PENGETAHUAN IBU TENTANG KEBIASAAN PEMBERIAN DOT SUSU TERHADAP KARIES GIGI PADA BALITA DI POSYANDU - Applonia Leu Obi; Pietrecina Moi (SINERGI : Jurnal Riset Ilmiah, 2026)
Background: Dental caries remains a common oral health problem among toddlers. One of the contributing factors is the habit of using feeding bottles or pacifiers, especially during sleep. Mothers’ knowledge regarding the impact of pacifier use on children’s oral health plays an important role in preventing dental caries. This study aimed to determine the relationship between mothers’ knowledge of pacifier-feeding habits and the incidence of dental caries among toddlers at Posyandu Sodamolek Lasiana, Kupang City. Methods: This quantitative study used a cross-sectional design involving 35 mothers of toddlers selected through total sampling. Data were collected using a knowledge questionnaire and an observation sheet for dental caries. Data were analyzed using the Chi-Square test with a significance level of α = 0.05. Results: Most mothers had a moderate level of knowledge (42.9%). The majority of toddlers used pacifiers while sleeping (74.3%), and 62.9% had dental caries. Chi-Square analysis showed a significant relationship between mothers’ knowledge and dental caries incidence (p = 0.021). Conclusion: Mothers’ knowledge is significantly associated with dental caries among toddlers. Oral health education for mothers should be strengthened to support early caries prevention.